ANALISIS PENGARUH VARIASI BEBAN TURBIN GAS TERHADAP EFISIENSI HEAT RECOVERY STEAMGENERATOR TIPE TRIPLE PRESSURE REHEAT UNIT 4.2PLTGU X - Reza Arnanda (2022)
Electricity needs are always changing because it is influenced by consumer demand. The changing demand for electrical energy consumption must be followed by the amount and availability of loads generated by the generator. PLTGU X often experiences load changes where these changes will affect the performance of other components, especially HRSG. HRSG is a tool to produce steam by utilizing the heat of exhaust gas from PLTG. Calculations using HRSG Unit 4.2 operational data on January 18, 2022 using load variations between 205 MW to 250 MW. The calculation process is carried out in theory and simulation using Cycle Tempo Release 5.0. From the calculation results, it is found that the variation of the gas turbine load can affect the performance of the HRSG. HRSG's energy efficiency decreases when it reaches high loads. Energy efficiency has increased from a load of 210 MW and then a downward trend occurs at a load of 220 MW to 250 MW. The HRSG's exergy efficiency also increases as the gas turbine load increases. The exergy efficiency of the steam turbine increases with the increase in the HRSG inlet gas temperature. Efficiency has an increasing trend from 594°C to 612.13°C. The temperature of the HRSG inlet gas affects the efficiency of the steam power cycle which increases with the increase in the temperature of the exhaust gas entering the HRSG. The heat transfer rate increases as the gas turbine load increases. The heat transfer rate increased from a load of 205 MW of 3702535 kJ/s to 250 MW of 4232602,069 kJ/s